2004
DOI: 10.1152/ajpregu.00558.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of white adipose tissue and its regulation of fat cell number

Abstract: . Sympathetic innervation of white adipose tissue and its regulation of fat cell number. Am J Physiol Regul Integr Comp Physiol 286: R1167-R1175, 2004 10.1152/ajpregu.00558.2003.-White adipose tissue (WAT) is innervated by the sympathetic nervous system (SNS), and the central origins of this innervation have been demonstrated for inguinal and epididymal WAT (iWAT and eWAT, respectively) using a viral transneuronal tract tracer, the pseudorabies virus (PRV). Although the more established role of this sympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
186
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(205 citation statements)
references
References 43 publications
14
186
5
Order By: Relevance
“…Paraventricular nucleus (PVN) CRH neurons innervate WAT directly (32,33). The PVN neurons that send projections to WAT are innervated by POMC neurons from the arcuate nucleus, which express MC3-R, and by NPY neurons in the nucleus of the solitary tract (31).…”
Section: Discussionmentioning
confidence: 99%
“…Paraventricular nucleus (PVN) CRH neurons innervate WAT directly (32,33). The PVN neurons that send projections to WAT are innervated by POMC neurons from the arcuate nucleus, which express MC3-R, and by NPY neurons in the nucleus of the solitary tract (31).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this fat-pad variation is not entirely clear, however, a likely explanation is that fat-pads differ in the density of sympathetic innervation 50,51 and/or cell-autonomous inducibility of molecular pathways of brown fat adipogenesis. 18 Supporting the former, it has been shown that the number of sympathetic nerve fibers correlates positively with the density of brown adipocytes in WAT 52 and that norepinephrine concentration varies among fat pads, being higher, for example, in retroperitoneal than epididymal fat pads in Siberian hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…18 Supporting the former, it has been shown that the number of sympathetic nerve fibers correlates positively with the density of brown adipocytes in WAT 52 and that norepinephrine concentration varies among fat pads, being higher, for example, in retroperitoneal than epididymal fat pads in Siberian hamsters. 50,51 With respect to cell-autonomous inducibility of molecular pathways of brown fat adipogenesis, it has been shown that mRNA expression of Prdm16 is higher in inguinal than epididymal fat pads in B6 mice, and that adipose tissue overexpression of Prdm16 on this genetic background results in emergence of brown-like adipocytes in inguinal but not in epididymal fat pads. 18 The retroperitoneal and inguinal fat pads (but not epididymal fat pads to our knowledge) showed emergence of brown fat (in response to cold or b 3 -stimulation) in several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adult male Siberian hamsters, ~3.5 months old and weighing 35-43 g were obtained from our breeding colony. The lineage of this colony has been described recently (Bowers et al, 2004). Hamsters were group-housed and raised in a long-day photoperiod (16:8 light: dark; lights on at 0200h) from birth.…”
Section: Animalsmentioning
confidence: 99%